Національна академія наук України: сучасний стан і наукові обрії майбутнього - Скрипник, Г. (Народна творчість та етнологія, 2023)
У статті розглядаються актуалізовані впродовж останнього десятиріччя проблеми оптимізації діяльності установ Національної академії наук України в контексті потреб реформування вітчизняної академічної науки. Йдеться про екзистенційні доленосні випробування та виклики, що постали перед українським народом унаслідок широкомасштабної російської військової агресії, а відтак – про потребу ефективного використання технічно-економічних ресурсів та інтелектуальної бази країни, підвищення ролі науки в безпеково-оборонній системі держави, употужнення інноваційної складової наукового потенціалу Національної академії наук України. У розвідці наголошується на зримих успіхах установ Національної академії наук України як у сфері теорій, так і в царині прикладних досліджень і технологій, підкреслюється факт, що значна частка вітчизняних наукових досягнень і винаходів належить дослідникам інститутів НАН України. Важливими державного значення є також напрацювання академічних гуманітарних інститутів, які постають базовими науковими осередками України з досліджень проблем мовознавства, мистецтвознавства, народознавства та літературознавства; з розроблення і формування засад нормативної бази функціонування української мови як державної; зі студіювання питань розвитку теорії та історії української мови; з укладання словникового фонду та створення довідниково-публікаційної продукції. Гуманітарним академічним інститутам належить заслуга підготовки та опублікування потужного корпусу історій народної та професійної культури, видання багатотомних енциклопедій та словників, що представляють високий художньо-естетичний потенціал культурно-мистецької спадщини українського народу. Водночас у статті наголошується на з’яві численних публікацій, автори яких прагнуть знецінити вітчизняну науку, знівелювати її здобутки й поставити під сумнів саме її подальше функціонування в рамках Національної академії наук. Авторка статті спростовує ці спроби як недалекоглядні, безпідставні та згубні для цивілізаційного поступу держави. Дослідниця зазначає, що національні науки визнаних світових країн є атрибутом їх цивілізаційного розвитку. Тому-то разом з пошуком шляхів модернізації академічної науки, її повноцінної інтеграції до світового наукового простору українському суспільству слід подбати про збереження її кадрового потенціалу, фінансову підтримку та употужнення науково-технічної бази. У статті обстоюється думка, що Академія наук має і надалі в період повоєнного відновлення зміцнювати свою роль як основного арбітра в окресленні перспектив розвитку держави, у зміцненні її оборонної спроможності та безпекових засад. The problems of optimizing the activities of the institutions of the National Academy of Sciences that have become relevant for the last decade are considered in the article in the context of the necessity to reform Ukrainian academic science. It concerns the existential fateful trials and challenges faced by the Ukrainian people as a result of a large-scale Russian military aggression, and therefore it is about the need for effective use of technical and economic resources and the intellectual base of the country, increasing the significance of science in the security and defense system of the state, and strengthening the innovative component of the scientific potential of the National Academy of Sciences of Ukraine. The visible successes of the institutions of the National Academy of Sciences of Ukraine, both in the field of theories and in the sphere of applied research and technologies, are emphasized in the study. Attention is also paid to the fact that a significant share of domestic scientific achievements and inventions belong to the researchers of the institutes of the National Academy of Sciences of Ukraine. The investigations of academic institutes in the humanities are considered to be of national importance. They have become the basic scientific centers of Ukraine for researching the problems of Linguistics, Art Studies, Ethnology and Literary Criticism; the development and formation of the essential principles of the normative framework for the functioning of the Ukrainian language as a state one; the study of issues of the development of the theory and history of the Ukrainian language; compiling a dictionary fund; and the creation of reference and published works. Humanitarian academic institutes have the merit of preparing and publishing a powerful corpus of stories of folk and professional culture, publishing multi-volume encyclopedias and dictionaries that represent the high artistic and aesthetic potential of the cultural and artistic heritage of the Ukrainian people. At the same time, it is emphasized in the article on the phenomenon of the appearance of numerous published works. Their authors seek to devalue domestic science, nullify its achievements, and cast doubt on the question of its very future functioning within the framework of the National Academy of Sciences. The authoress of the submitted article refutes these attempts as shortsighted, baseless, and detrimental to the civilizational progress of the state. The researcher notes that the national sciences of recognized world countries are an attribute of their civilizational development. Therefore, along with the search for ways to modernize academic science's full integration into the world scientific space, Ukrainian society should take care of the preservation of its personnel potential, financial support, and strengthening of the scientific and technical base. The opinion that the Academy of Sciences should continue to reinforce its significance as the main arbiter in defining the development prospects of the state, intensify its defense capacity and security foundations, during the period of post-war reconstruction is grounded in the article.